Auditoría general con enfoque integral a la institución educativa Baudilio Montoya del municipio de Calarcá Quindío para la vigencia 2011 (2012)
This paper contains an audit Regular on the Educational Institution Baudilio Montoya Calarcá Township Quindio by the Comptroller General of Quindio as control and monitoring body, the process focuses on the audit and budget of the Educational Institution; this activity is due to the increasing need for control in educational institutions, which seeks to ensure the proper use and management of public assets and resources, as a method of obtaining evidence, we performed direct verification of the documents supports the management made to the Educational Institution Baudilio Montoya in different areas of process management evaluated.